Commercialization of Campus Waste-Derived Product at UPN “Veteran” Jawa Timur - Sitogasa, Praditya S. Ardisty; Rosariawari, Firra (Nusantara Science and Technology Proceedings, 2023)
Universitas Pembangunan Nasional (UPN) "Veteran" Jawa Timur is one of the state universities located in the Rungkut Madya-Gunung Anyar area, Surabaya, where various activities take place daily. Based on the types of activities, the sources of waste at UPN "Veteran" Jawa Timur are divided into two areas: waste from academic buildings, offices, and cafeterias, and waste from gardens and streets. About 70% of the waste generated by campus activities has the potential for recovery. Organic waste from garden sweeping, cafeterias, and other activities can be processed through composting. In addition to composting, there is currently another alternative method with better economic potential, one of which is turning it into eco-enzymes. Commercialization is understood as a process of developing new products from creative industries, making a product more valuable and commercially viable. In this article, commercialization is also understood as a comprehensive technology transfer process, starting from selecting raw materials for a product and continuing through the production process until the product is produced and reaches the end consumer. With the available and applicable processing technologies, it is hoped that this commercialization activity can assist in promoting the transformation of waste into furniture, home décor, and eco-enzymes by business groups. It includes designing commercial packaging for products and creating management and promotion schemes for processed campus waste products at UPN "Veteran" Jawa Timur.